ESG and firm performance: do stakeholder engagement, financial constraints and religiosity matter? - Ly Ho; Van Ha Nguyen; Tung Lam Dang (Journal of Asian Business and Economic Studies)
Purpose – This study revisits the relationship between environmental, social and governance (ESG) activities and firm performance. More importantly, it tests whether this relationship is moderated by critical yet underexplored factors such as stakeholder engagement, financial constraints, and religiosity. Design/methodology/approach – A wide range of estimation techniques, including pooled ordinary least squares (OLS), fixed effects, system generalized method of moments (GMM) and propensity score matching-difference-in-differences (PSM-DiD), are employed to investigate such issues in a large sample of firms from 31 countries. Findings – ESG performance has a positive and significant impact on firm performance. While stakeholder engagement positively moderates this relationship, financial constraints and religiosity negatively moderate it. Interestingly, this positive linkage is driven by environmental and social performance rather than governance performance. Practical implications – Firms should proactively engage in ESG initiatives and consider the intervening influences of stakeholder engagement, financial constraints and religiosity in making decisions to invest in ESG activities. Furthermore, our findings can help policymakers understand the financial consequences of ESG practices, which can be helpful in designing new policies to further promote corporate engagement in ESG practices. Originality/value – First, our research findings help reconcile the long-standing debate about the value impact of ESG. Second, our paper investigates relatively new aspects of the ESG-firm performance relationship. Third, our study offers more insight into the ESG literature by showing that not all ESG dimensions equally impact firm performance.